2013
DOI: 10.3109/00365548.2013.837957
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid penetration of tigecycline

Abstract: We report, in a clinical setting, the tigecycline concentration and area under the concentration-time curve (AUC) - both in blood and in cerebrospinal fluid (CSF) - of a patient with a ventriculo-atrial shunt infection. Tigecycline weakly penetrates CSF the CSF-to-serum concentration ratio was 0.079 and CSF-to-serum AUC(0-12) ratio was 0.067.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 6 publications
1
23
1
Order By: Relevance
“…Intravenous tigecycline for treatment of our patient resulted in poor efficacy despite it being performed in accordance with the instructions, but intrathecal injection enabled tigecycline to fully exert its therapeutic effect, restoring CSF to a completely normal state within 6 days. The treatment outcome suggests that intravenous tigecycline could not reach the minimum inhibitory concentration in the CSF as previously reported 5 6…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Intravenous tigecycline for treatment of our patient resulted in poor efficacy despite it being performed in accordance with the instructions, but intrathecal injection enabled tigecycline to fully exert its therapeutic effect, restoring CSF to a completely normal state within 6 days. The treatment outcome suggests that intravenous tigecycline could not reach the minimum inhibitory concentration in the CSF as previously reported 5 6…”
Section: Discussionsupporting
confidence: 70%
“…Treatment of the disease can be very difficult. It has been shown that intravenous infusion of tigecycline results in low cerebrospinal fluid (CSF) concentrations,5 6 and it fails to achieve a clinical response in the treatment of A baumannii cerebritis 5…”
Section: Introductionmentioning
confidence: 99%
“…HPLC has been extensively used for the estimation of TIG in biological samples (Rodvold et al, 2006, Ji et al, 2007, Pallotto et al, 2014, Xie et al, 2014. However, relatively few parameters, such as mobile phase composition, analysis time, reproducibility, detection limit and obtaining a suitable IS, have been reported, making it difficult for these few methods to be used for widespread applications (Xie et al, 2014).…”
Section: Application Of Method: Brain Distribution Studiesmentioning
confidence: 99%
“…TIG concentrations were lower when compared with those of other drugs in the tetracycline family and it was concluded that inflamed meninges may facilitate the drug's penetration of the CSF (Nau et al ., ). In a couple of cases, the CSF concentrations were determined to be lower than the minimum inhibitory concentration (MIC) (Lengerke et al ., , Pallotto et al ., ), but in most of the reported cases they were constantly above the MIC (Pankey and Ashcraft, , Ray et al ., , Dandache et al ., ). These results warrant further investigations into the neuroprotective properties of TIG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation